Translation and validation of the Arabic Jordanian version of the diabetic foot ulcer scale-short form (DFS-SF) - Alzghoul, Obada Twffeg; Othman, Ahmad Tajuddin; Aman, Rahimi Che (Edelweiss Applied Science and Technology, 2024)
The Diabetic Foot Ulcer Scale-Short Form (DFS-SF) is an important tool for assessing the quality of life of diabetic foot patients. This study aims to translate and validate the DFS-SF into Arabic and evaluate its validity and reliability. The translation process followed WHO guidelines, including forward translation, expert panel review, back translation, pre-testing, and final version development. The translated questionnaire was then administered to a sample of Arab Jordanian patients with diabetic foot ulcers. Validity was assessed by examining the correlation coefficients between each item and its corresponding dimension, as well as its correlation with the DFS-SF scale as a whole. Reliability was evaluated using Cronbach's alpha coefficient. The results demonstrated high validity and reliability of the Arabic Jordanian version of the DFS-SF, making it a valuable tool for assessing the impact of diabetic foot ulcers on patients' quality of life.